2000
DOI: 10.1038/modpathol.3880007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Her-2/Neu Status in Breast Carcinoma: Comparative Analysis of Immunohistochemistry and Fluorescent In Situ Hybridization

Abstract: Her-2/neu (H2N) status in breast carcinoma has been considered a prognostic factor that may have therapeutic implications; however, the correlation between H2N overexpression and gene amplification has not been completely defined. A consecutive series of ductal carcinomas (34 invasive and 7 in situ) were analyzed by fluorescent in situ hybridization for H2N gene and chromosome 17 copy number using touch preps of intact cells and by immunohistochemistry, using three different commercial antibodies to H2N protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
121
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(133 citation statements)
references
References 16 publications
9
121
2
1
Order By: Relevance
“…Press et al (26) found FISH to be 98% sensitive and 100% specific compared with PCR and that FISH results were an independent predictor of poor outcome. Similar data showing concordance between IH and FISH were obtained by P. Jimminez et al (27) and Jacobs et al (28). These studies suggest that very few cases (3-5%) show protein overexpression without gene amplification indicating that FISH or PCR could be false negative in about 5% of cases.…”
Section: Discussionsupporting
confidence: 82%
“…Press et al (26) found FISH to be 98% sensitive and 100% specific compared with PCR and that FISH results were an independent predictor of poor outcome. Similar data showing concordance between IH and FISH were obtained by P. Jimminez et al (27) and Jacobs et al (28). These studies suggest that very few cases (3-5%) show protein overexpression without gene amplification indicating that FISH or PCR could be false negative in about 5% of cases.…”
Section: Discussionsupporting
confidence: 82%
“…Farabegoli et al (28), obtained a correlation of only 72% between FISH and IHC in a study of 79 primary invasive breast carcinoma samples, because of the observation of an excess of immunopositive cases without amplification. Similarly, Jimenez et al (32) observed, in a comparative study of 41 cases, a proportion of 3 to 15% of cases, according to the antibody used, showing moderate immunostaining without amplification. Jacobs et al (29), in a study of 100 consecutive paraffinembedded breast carcinomas samples, demonstrated a concordance of 92% between the results of FISH and IHC, using the Oncor Inform kit and the Dako A485 polyclonal antibody.…”
Section: Discussionmentioning
confidence: 64%
“…Slamon et al (2) have shown the existence of a direct correlation between amplification and overexpression of ERBB2. However, Press et al (32) have stressed the variability of the sensitivity of HER-2/neu antibodies as potential source of errors in the assessment of the expression of the gene. The present controversy about the reliability of a U. S. Food and Drug Administration-approved HER-2/ neu IHC test (33)(34) illustrates that this issue remains incompletely solved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This score is basically similar to those used for breast cancers (17, 18) except 1ϩ. Many studies have chosen to ignore the cytoplasmic staining (18,19); however, we tentatively included this in 1ϩ, because it was virtually impossible to differentiate faint membranous staining from cytoplasmic staining in several cases and to compare previous findings using similar standards.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%